2008
DOI: 10.1111/j.1471-4159.2008.05537.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β‐catenin signalling by GSK‐3 inhibition increases p‐glycoprotein expression in brain endothelial cells

Abstract: This study investigates involvement of β-catenin signalling in regulation of p-glycoprotein (p-gp) expression in endothelial cells derived from brain vasculature. Pharmacological interventions that enhance or that block β-catenin signalling were applied to primary rat brain endothelial cells and to immortalized human brain endothelial cells, hCMEC/D3, nuclear translocation of β-catenin being determined by immunocytochemistry and by western blot analysis to confirm effectiveness of the manipulations. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
114
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 32 publications
(62 reference statements)
6
114
1
Order By: Relevance
“…(19) Also, the regulation of P-gp expression can be influenced by b-catenin signaling. (20) Our data confirmed that SATB1 could significantly elevate the level of ErbB2 (data not shown), which may be due to P-gp upregulation in cell lines in which SATB1 is highly expressed. The regulation of MDR1 expression in tumor cells involves a complex interplay of multiple factors.…”
Section: Discussionsupporting
confidence: 77%
“…(19) Also, the regulation of P-gp expression can be influenced by b-catenin signaling. (20) Our data confirmed that SATB1 could significantly elevate the level of ErbB2 (data not shown), which may be due to P-gp upregulation in cell lines in which SATB1 is highly expressed. The regulation of MDR1 expression in tumor cells involves a complex interplay of multiple factors.…”
Section: Discussionsupporting
confidence: 77%
“…The stabilization of ß-catenin might finally A c c e p t e d M a n u s c r i p t 19 be transmitted into enhanced expression of the investigated ABC-transporters as it was shown for P-gp in brain endothelial cells that its promoter can be activated by ß-catenin signaling [43]. Since expression of BCRP and MRP-2 increased under activation of canonical Wnt/ß-catenin signaling as well [43] it can be suggested that stabilized ß-catenin activates a number of ABC-transporters by promoter activation.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of Wnt/GSK3/b-catenin axis is known to increase the expression of Pgp in hCMEC/D3 cells. 2,3,6 The activation of RhoA and RhoAK is known to enhance the Pgp activity in BBB cells. 11 It is not known: (1) whether the Wnt/RhoA/ RhoAK axis controls also the Pgp expression; (2) whether the canonical and non-canonical Wnt pathways cooperate in regulating the Pgp levels in BBB cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 P-glycoprotein (Pgp) is one of the ATP binding cassette transporters present on the luminal side of BBB cells: it effluxes back into the bloodstream several chemotherapeutic drugs (e.g., anthracyclines, taxanes, Vinca alkaloids, epipodophyllotoxins, topotecan, methotrexate, imatinib, dasatinib, lapatinib, gefitinib, sorafenib, erlotinib), analgesics, anti-epileptics, anti-retrovirals, and antibiotics. 1 The Wnt signaling has a central role in regulating the expression of Pgp in BBB cells 2,3 and relies on the simultaneous activation of different intracellular transducers. In the so-called 'Wnt canonical pathway', the soluble Wnt proteins bind to the Frizzled receptor and the low-density lipoprotein receptor-related protein-5 and -6 co-receptors, reduces the activity of glycogen synthase kinase 3 (GSK3), allowing the release of b-catenin from the cytosolic adenomatous polyposis coli-axin complex and its translocation into the nucleus.…”
Section: Introductionmentioning
confidence: 99%